To Study Etiology and Clinico-Radiological Profile of Patients presenting with Pleural Effusion - Vishal Chopra; Mohan V; Bansal A; Kaur P; Anu (GMC Patiala Journal of Research and Medical Education, 2018)
Pleural effusion is the abnormal accumulation of fluid in the pleural space. Pleural effusions are either transudates or exudates based on the biochemical characteristics of the fluid, which usually reflect the physiologic mechanism of its formation. This prospective study was carried out to access the etiology and to know the clinico-radiological profileof 130 patients presenting with pleural effusions over a period of one yearin the Department of Pulmonary Medicine, GMC, Patiala, India. In our study, out of 6 patients of transudative pleural effusions, 83.33% were males and 16.67% were females, whereas out of 124 patients of exudative pleural effusions, 74.19% were males and 25.81% were females. Tuberculosis (70.16%) was the most common condition associated with exudative effusions followed by para-pneumonic effusions (15.32%) and malignant pleural effusions (12.10%), whereas transudative effusions were associated with either congestive heart failure (50%) or renal disease (50%).Commonest clinical symptom was cough (73.85%), followed by chest pain (60.77%) or fever (55.38%). Thus patients presenting with these complaints should always be evaluated for the presence of pleural effusion for early diagnosis.